2002
DOI: 10.1097/00001888-200211000-00023
|View full text |Cite
|
Sign up to set email alerts
|

Performance-based Assessment of Internal Medicine Interns

Abstract: This exercise has given the faculty a detailed view of baseline clinical and written documentation skills of our entering interns. Overall, the residents demonstrated at least minimal competency in history taking and communication skills, but not in performing the expected focused physical exam. Their written reports showed adequate documentation of historical items but not of pertinent physical findings. The interns did not consistently make a problem list, provide a differential diagnosis, or show clinical r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…When immediate feedback on performance is provided, OSCEs can be formative in developing skills and enhancing knowledge 17,18 . Objective structured clinical exams are widely used in residency training disciplines, including internal medicine, 19,20 surgery, 12 pediatrics, 21 rehabilitation medicine, 22 psychiatry, 23,24 and family medicine 25 . They have also been used to teach and assess specialized skills such as delivering bad news, 26 addressing advanced care directives, 27 demonstrating cultural competence, 28 and ethical decision making 29 …”
mentioning
confidence: 99%
“…When immediate feedback on performance is provided, OSCEs can be formative in developing skills and enhancing knowledge 17,18 . Objective structured clinical exams are widely used in residency training disciplines, including internal medicine, 19,20 surgery, 12 pediatrics, 21 rehabilitation medicine, 22 psychiatry, 23,24 and family medicine 25 . They have also been used to teach and assess specialized skills such as delivering bad news, 26 addressing advanced care directives, 27 demonstrating cultural competence, 28 and ethical decision making 29 …”
mentioning
confidence: 99%
“…Several studies have previously discussed the importance of documentation skills of the medical history interview in medical education and have evaluated documentation skills by medical students showing deficiencies in this competency 12–15 . A documentation analysis was also carried out with postgraduate clinicians 16 .…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11] Several studies have previously discussed the importance of documentation skills of the medical history interview in medical education and have evaluated documentation skills by medical students showing deficiencies in this competency. [12][13][14][15] A documentation analysis was also carried out with postgraduate clinicians. 16 However, clinicians may focus on a more efficient approach, in comparison with a more complete and systematic approach during medical school.…”
mentioning
confidence: 99%
“…Taking an adequate history and physical examination that suggest possible differential diagnoses are very important, so that without an adequate history and physical examination, all the subsequent diagnostic investigations might be misleading [2]. Despite its importance, significant weaknesses in the diagnostic skills among medical students, residents, and practicing physicians have been consistently reported [3,4]. Studies have shown that the most common error in the diagnostic reasoning of medical students and novice physicians is the use of non-discriminatory clinical findings (i.e.…”
Section: Introductionmentioning
confidence: 99%